Application of experimental design techniques in manufacturing [electronic resource] - 423254 Liw, Han Wei (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Pembuatan)) - Universiti Teknologi Malaysia, 2008